2019
DOI: 10.21098/jimf.v4i2.964
|View full text |Cite
|
Sign up to set email alerts
|

The Single Currency for Islamic Nations: Do Heterogeneities Matter?

Abstract: The purpose of this study is to assess the readiness of 44 OIC member countries to form a currency union and to test whether the Optimum Currency Area (OCA) criteria remain relevant to a large region like the OIC. Large geographic size is subject to socio-economic and geographic disparities. This study employs the OCA-index to estimate the degree of readiness of the OIC to form a currency union. Five selected criteria –business cycle synchronization, trade openness, inflation similarity, the size of the econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Only 20 percent of country pairs are nominated in the little integration. This finding clearly proves an empirical gap compared to previous studies (Bayoumi & Mauro 2001;Ng 2002;Huang & Guo 2006;Achsani & Partisiwi 2010;Lee 2011;Agustiar 2018). Indonesia's monetary integration has so far been considered somewhat weak against its neighbouring countries, but this study found it to be strongly integrated with more than half of the OIC countries.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Only 20 percent of country pairs are nominated in the little integration. This finding clearly proves an empirical gap compared to previous studies (Bayoumi & Mauro 2001;Ng 2002;Huang & Guo 2006;Achsani & Partisiwi 2010;Lee 2011;Agustiar 2018). Indonesia's monetary integration has so far been considered somewhat weak against its neighbouring countries, but this study found it to be strongly integrated with more than half of the OIC countries.…”
Section: Resultssupporting
confidence: 73%
“…Two regional economic blocs in Africa -Central Africa and West Africa -have set the CFA Franc as a benchmark since 1945 (Uzonwanne 2012). In the context of Indonesia, previous studies reported that the synchronization of the Indonesian Rupiah (IDR) with other countries is relatively weak (Bayoumi & Mauro 2001;Ng 2002;Huang & Guo 2006;Achsani & Partisiwi 2010;Lee 2011;Agustiar 2018). The weakness of Indonesia's integration with its neighbouring countries is primarily due to the instability of prices, currency asymmetry, low trade openness, and a business cycle that is non-synchronous with the global economy.…”
Section: Introductionmentioning
confidence: 99%
“…15. Surprisingly in a different context, Agustiar (2018) found that most of the OIC countries are ready to form a currency union together as the socio-economic gaps across member countries tend to decline over time.…”
Section: Notesmentioning
confidence: 98%